The impact of red blood cell storage duration on clinical outcomes in pediatric cardiac surgery: a systematic review and meta-analysis - Jin, Xing; Zhang, Qingyu; Sun, Ye; Dong, Zhiting; Jin, Wenzhe (Frontiers in Pediatrics, 2025)
BackgroundThe impact of red blood cell (RBC) storage duration during cardiopulmonary bypass (CPB) priming in pediatric cardiac surgery remains unclear.ObjectiveTo evaluate whether RBC storage time affects perioperative outcomes in children undergoing cardiac surgery.MethodsWe performed a systematic review and meta-analysis of studies comparing fresh vs. longer-stored RBCs for CPB priming in pediatric patients. Databases searched included PubMed, EMBASE, Cochrane Library, and Web of Science (through May 2025). Primary outcomes were mortality, infection/sepsis, respiratory complications, and multiple organ dysfunction syndrome (MODS); secondary outcomes included mechanical ventilation duration, ICU stay, and intraoperative lactate levels.ResultsTen studies (including one randomized controlled trial) were included. No significant differences were found between groups in any primary or secondary outcomes, except for a slightly shorter ICU stay in the fresh RBC group (mean difference = –1.08 days), with high heterogeneity.ConclusionsRBCs stored within standard durations appear safe for CPB priming in pediatric cardiac surgery. These findings support current transfusion practices and underscore the need for further high-quality randomized trials.Systematic Review Registrationhttps://www.crd.york.ac.uk/prospero/display_record.php?RecordID=1015198, PROSPERO CRD420251015198.